THIS ISN’T MY CRASH BANDICOOT - A Critical Analysis of Character Redesign in Video Games - Bruzzi, Lucas Macedo; Mota, Rosilane Ribeiro da (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2023: Anais Estendidos do XXII Simpósio Brasileiro de Jogos e Entretenimento Digital, 2023)
It’s common for the look of game characters to change over the years and adapt to reach new audiences. This research was developed to understand which artistic aspects should be taken into consideration to create a more believable character redesign using Crash Bandicoot as the subject of analysis. This article analyses two distinct redesigns of the same video game character and compares them to the first designs, comparing different artistic elements like conceptualization, workflow and execution.